2008
DOI: 10.5194/npg-15-567-2008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of phase coherence in fully developed atmospheric turbulence: Amazon forest canopy

Abstract: Abstract. In a recent paper it was shown that the intermittent nature of solar wind turbulence can be characterized by kurtosis and phase coherence index. In this paper, we apply these two nonlinear time series techniques to characterize the intermittent nature of atmospheric turbulence above and within the Amazon forest canopy using the day-time data of temperature and vertical wind velocity measured by a micrometeorological tower at two different heights. By applying kurtosis and phase coherence index to qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Observational evidence in support of this finding in space plasma turbulence was obtained by Hada et al (2003), Koga and Hada (2003) and Koga et al (2007Koga et al ( , 2008 using the Geotail solar wind data upstream and downstream of Earth's bow shock, by Sahraoui (2008) using the Cluster data in the magnetosheath close to the Earth's magnetopause, and by Telloni et al (2009) using the SOHO data of solar corona; and in atmosphere turbulence by Chian et al (2008) using the Amazon forest data.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Observational evidence in support of this finding in space plasma turbulence was obtained by Hada et al (2003), Koga and Hada (2003) and Koga et al (2007Koga et al ( , 2008 using the Geotail solar wind data upstream and downstream of Earth's bow shock, by Sahraoui (2008) using the Cluster data in the magnetosheath close to the Earth's magnetopause, and by Telloni et al (2009) using the SOHO data of solar corona; and in atmosphere turbulence by Chian et al (2008) using the Amazon forest data.…”
Section: Introductionmentioning
confidence: 80%
“…5. An alternative method of quantifying intermittency and non-Gaussianity is to apply the phase coherence technique using surrogate data by defining a phase coherence index Koga and Hada, 2003;Koga et al, 2007Koga et al, , 2008Nariyuki and Hada, 2006;Chian et al, 2008;Nariyuki et al, 2008;Sahraoui, 2008;Telloni et al, 2009) …”
Section: Introductionmentioning
confidence: 99%
“…For example, the imperfect phase synchronization of the fundamental spectral components with distinct scales in fluids and plasmas can be the origin of the intermittent bursts of wave energy in turbulence (He and Chian, 2003). There is finite phase coherence in wave interactions in turbulence, as evidenced in the magnetic field turbulence observed upstream of the Earth's bow shock and in the ambient solar wind (Koga et al, 2007;Chian and Miranda, 2009) and in the fluid turbulence observed in the Earth's atmosphere (Chian et al, 2008).…”
Section: Chaos and Turbulencementioning
confidence: 98%
“…Turbulent flows in canopies are dominated by such coherent structures of whole canopy scale [12], which might be responsible for up to 75% of the turbulent fluxes in the atmospheric surface layer [13]. Coherent structures have received close attention from turbulence researchers investigating flow dynamics in the atmospheric boundary layer over the past few decades [11,[14][15][16][17][18][19][20][21]. Atmospheric turbulence possesses temporal and spatial scales that range over many orders of magnitude, and the large-scale turbulence (such as coherent structures) is known to have drastic impact on the statistical parameters of the small-scale turbulence [22].…”
Section: Introductionmentioning
confidence: 99%